On the Distribution and Acquisition of the West Germanic 'Need'-Verbs: German between Dutch and English. Issue 4 (11th November 2016) - Lin, Jing
Abstract : This paper investigates three verbs expressing necessity in the three West Germanic languages: Dutch hoeven, English need, and German brauchen . These three verbs are all categorized as negative polarity items(npis) . However, there are differences in their distribution as NPIs, which posit German brauchen between English need and Dutch hoeven. By analyzing two factors that may influence acquisition, namely, opacity and input frequency, this paper moreover presents a similar pattern for the acquisition of these NPIs: The Dutch NPI hoeven emerges earlier in child language than its German counterpart, which in turn arises earlier than the English NPI need .